SURVEY FOR FUSARIUM WILT INCIDENCE OF TOMATO IN MAJOR CROP GROWING AREAS OF TELANGANA STATE - and G. ANITHA KUMARI, CH. S. KISHORE KUMAR, BHARATHI N BHAT, R. JAGADEESHWAR, CH.V. DURGA RANI (The Journal of Research, PJTSAU, 2021)
Tomato (Lycopersicum esculantum Mill.), aÂ â€œfruity vegetableâ€, native of Peru, South America, is aÂ popular and widely grown vegetable crop cultivatedthroughout the world. It is also known as poor manâ€™sÂ apple due to the availability of vitamin C, mineralsÂ (Fe and Cu) and antioxidants in moderate quantitiesÂ with generally low dietary nutrients. It is an annualÂ vegetable crop growing to a height of 1-3 m, with weakÂ woody stem (Naika et al., 2005), bearing edible fruitsÂ belonging to the family Solanaceae having more thanÂ 3000 species. Tomato crop is affected by severalÂ diseases incited by organisms like fungi, bacteria andÂ viruses etc., which affects plant growth and yield.Â Among the fungal diseases that affect tomato,Â Fusarium wilt caused by Fusarium oxysporum f. sp.Â lycopersici (Sacc.), Snyder and Hans, is one of theÂ most serious and destructive diseases across the worldÂ (Sheu and Wang, 2006) with severe economic lossÂ wherever tomato is grown ( Sudhamoy et. al., 2009).